2014
DOI: 10.5505/bsbd.2014.36035
|View full text |Cite
|
Sign up to set email alerts
|

Opinions and suggestions of nurses about internship

Abstract: ÖZET AMAÇ: Yeni intörnlük programı kapsamında, uygulamanın yapıldığı kliniklerde ebe ve hemşire öğrencilerle birlikte görev yapan hemşirelerin katkı ve görüşlerini belirlemek amacıyla yapılmıştır. YÖNTEMLER: OMÜ Tıp Fakültesi Hastanesinde görev yapan klinik hemşirelere anket yapılarak toplanmıştır. Hastanede öğrencilerin uygulamada bulunduğu kliniklerde görev yapan 220 hemşire evreni oluşturmuş olup, araştırmaya katılmayı kabul eden 137 hemşire örneklemi oluşturmuştur. Veriler, intörn uygulama sonunda araştırm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Chan also reported that internship clinical education projects improved the clinical skills and knowledge of nursing students and clinical nurses (26). Other studies also showed that cooperation of nurses and internship students improved nursing students' clinical knowledge, practical and communication skills, and selfconfidence under the influence of nurses (19,27).…”
Section: Discussionmentioning
confidence: 93%
“…Chan also reported that internship clinical education projects improved the clinical skills and knowledge of nursing students and clinical nurses (26). Other studies also showed that cooperation of nurses and internship students improved nursing students' clinical knowledge, practical and communication skills, and selfconfidence under the influence of nurses (19,27).…”
Section: Discussionmentioning
confidence: 93%
“…Most of the studies (60%) with sample numbers ranging from 76 to 326 were evaluated about internship model applied for the first time. During the internship process, students stated that their self-confidence increased (Şentürk Erenel et al, 2008;Tural Büyük et al, 2014), likewise nurses reported that students' confidence and adaptation to the profession increased (Şentürk Erenel ve ark., 2008). With the internship training it was stated that the quality of nursing care increased, work stress and workload decreased (Gökalp, Durmaz & Sevcan, 2018).…”
mentioning
confidence: 99%